2019
DOI: 10.1029/2019jd030679
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Changes in the Northern Midwinter Middle Atmosphere in Relation to the Quasi‐Biennial Oscillation

Abstract: Long‐term changes in the middle atmosphere due to anthropogenic greenhouse gas emissions are examined in relation to the effect of the equatorial Quasi‐Biennial Oscillation (QBO) on the northern midwinter circulation. The examinations are based on the Coupled Model Intercomparison Project Phase 5 simulations for 1979–2100 with the Earth‐System‐Model MPI‐ESM‐MR that generates the QBO internally. In particular, the three‐dimensional residual circulation is used as proxy for the Brewer‐Dobson circulation, reveali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
(156 reference statements)
0
6
1
Order By: Relevance
“…The weakening amplitude of the QBO cycle in most models and the MME can be explained by the increase in tropical upwelling accompanied with a strengthening Brewer‐Dobson circulation in response to more accumulated greenhouse gas concentration (Butchart et al, 2006; Kawatani et al, 2011; Kawatani & Hamilton, 2013). Although Gabriel (2019) identified that the QBO remains nearly unchanged in MPI‐ESM‐MR, we find that the QBO amplitude weakens in this model (Figure 4g). Latest studies provide more evidence that the QBO amplitude will weaken in the high‐emission scenario and 4 × CO 2 simulations (Butchart et al, 2020; Giorgetta, 2005; Richter, Anstey, et al, 2020; Richter, Butchart, et al, 2020), although our results further reveal that the QBO will also weaken in the moderate‐emission scenario and that the amplitude of the QBO easterlies will weaken more than that of the westerlies.…”
Section: Qbo Amplitude Changes In Historical and Future Simulationscontrasting
confidence: 72%
See 2 more Smart Citations
“…The weakening amplitude of the QBO cycle in most models and the MME can be explained by the increase in tropical upwelling accompanied with a strengthening Brewer‐Dobson circulation in response to more accumulated greenhouse gas concentration (Butchart et al, 2006; Kawatani et al, 2011; Kawatani & Hamilton, 2013). Although Gabriel (2019) identified that the QBO remains nearly unchanged in MPI‐ESM‐MR, we find that the QBO amplitude weakens in this model (Figure 4g). Latest studies provide more evidence that the QBO amplitude will weaken in the high‐emission scenario and 4 × CO 2 simulations (Butchart et al, 2020; Giorgetta, 2005; Richter, Anstey, et al, 2020; Richter, Butchart, et al, 2020), although our results further reveal that the QBO will also weaken in the moderate‐emission scenario and that the amplitude of the QBO easterlies will weaken more than that of the westerlies.…”
Section: Qbo Amplitude Changes In Historical and Future Simulationscontrasting
confidence: 72%
“…Gabriel (2019) suggests that the extratropical QBO signature changes toward the disappearance of the HT relationship based on one model, but we use a larger model ensemble and find a strengthened HT relationship. The different conclusions between Gabriel (2019) and this study might be caused by their different projected background circulations, periods of interest, model numbers, and experiment setups.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…J. Gray et al, 2003;Hamilton, 1998;Holton & Austin, 1991;Naito et al, 2003;Niwano & Takahashi, 1998;O'Sullivan & Dunkerton, 1994;O'Sullivan & Young, 1992), with an increase in interest during the last decade (e.g., Anstey et al, 2021;Elsbury et al, 2021;Gabriel, 2019;Garfinkel et al, 2012;Hansen et al, 2013;Naoe & Yoshida, 2019;Rao et al, 2020;Watson & Gray, 2014). Anstey et al (2021) examined the H-T relationship using a multi-model ensemble of QBO-resolving atmospheric general circulation models and reconfirmed the H-T relationship, but found it to be weaker than the observed response.…”
Section: The Holton-tan Effect and The Stratospheric Pathwaymentioning
confidence: 99%
“…Both parts of the BDC are caused by the action of atmospheric waves of various spatial and temporal scales [43]. In three-dimensional consideration, the Euler approach is used with timeaveraged (but not longitude-averaged) and vortex components [44,45].…”
Section: Stratospheric Meridional Circulationmentioning
confidence: 99%